Influence of growth parameters on the dopant configuration of nitrogen-doped graphene synthesized from phthalocyanine molecules - Shyaga N.; Sharma R.; Hassan N.; Alam M.B.; Parmar A.S.; Lahiri J. (My University, 2025)
Synthesis of nitrogen-doped graphene (NDG) via chemical vapor deposition (CVD) using phthalocyanine, a solid precursor containing carbon and nitrogen, is reported. The effect of the growth parameters (temperature, time, and carrier gas) on the surface morphology, dopant configuration, and conductivity of the films was studied. The NDG films were synthesized at different substrate temperatures of 1050 °C, 950 °C, and 850 °C for different growth times of 5–15 min in the presence of an Ar + H2 gas mixture. Significantly, pyrrolic-N type defects are observed predominantly after 5 min of growth time. At 1050 °C, pyrrolic N content is around 45.4% after 5 min of growth which decreased to 24.1% after 15 min of growth, while the graphitic-N content increased from 41.2 to 76% at the same time. It is demonstrated that the conversion of pyrrolic type of nitrogen to graphitic nitrogen defects can be arrested by changing the carrier gas from Ar + H2 to Ar. The pyrrolic-N content increased to 64% by changing the gas from Ar + H2 to Ar at 15 min. The electrolyte gated field-effect transistors were fabricated using the obtained films, and dopant-dependent mobility was observed. The mobility for pyrrolic-N-dominated film is 13.6 cm2 V−1 s−1 increasing to 62.8 cm2 V−1 s−1 for graphitic-N-dominated film. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.